An Anti-hTNF-α Variable New Antigen Receptor Format Demonstrates Superior in vivo Preclinical Efficacy to Humira® in a Transgenic Mouse Autoimmune Polyarthritis Disease Model - Ubah, Obinna C.; Steven, John; Porter, Andrew J.; Barelle, Caroline J. (Frontiers in Immunology, 2019)
Tumour necrosis factor-alpha (TNF-α), an established pro-inflammatory cytokine plays a central role in the induction and progression of several chronic inflammatory and autoimmune diseases. Targeting TNF-α as a treatment modality has shown tremendous success, however there are several limitations associated with the current anti-TNF-α biologic drugs including: immunogenicity, life-threatening infections, resistance to treatment, complexity of manufacture and cost of treatment. Here, we report the in vivo efficacy of novel anti-TNF-α formats generated from molecular engineering of variable new antigen receptors (VNARs), originally derived from the immune system of an immunised nurse shark. Two anti-TNF-α VNAR formats, a tandem multivalent trimer, D1-BA11-C4 and an Fc-fused quadrivalent D1-Fc-C4 (Quad-X™) construct were tested in a clinically relevant, preclinical mouse efficacy model of polyarthritis (Tg197) and compared to the commercial anti-TNF-α ‘best in class’ therapy, Adalimumab (Humira®). Both VNAR formats bind and neutralise anti-TNF-α through an epitope that appears to be different from those recognised by other anti-TNF biologics used clinically. All doses of Quad-X™, from 0.5 mg/kg to 30 mg/kg, significantly blocked the development of polyarthritis. At 0.5 mg/kg Quad-X™, the arthritis score was improved by 76% and the histopathology score by 63%. At 3 mg/kg Quad-X™, control of disease was almost complete at 90% (arthritis) and 88% (histopathology). In marked contrast, 1 mg/kg Humira® saw profound disease breakthrough with scores of 39% and 16 % respectively, increasing to a respectable 82% and 86% inhibition at 10 mg/kg Humira®. We have previously reported the superior potency of anti-TNF-α VNARs in vitro and in these studies translate this superiority into an in vivo setting and demonstrate the potential of VNAR formats to meet the requirements of next-generation anti-TNF-α therapies.